2016
DOI: 10.1186/s12889-016-2879-2
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and the determinants of obesity: a population-based survey of sixth grade school children in Taiwan

Abstract: Background: Health literacy has become an important health policy and health promotion agenda item in recent years. It had been seen as a means to reduce health disparities and a critical empowerment strategy to increase people's control over their health. So far, most of health literacy studies mainly focus on adults with few studies investigating associations between child health literacy and health status. This study aimed to investigate the association between health literacy and body weight in Taiwan's si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 20 publications
3
65
1
9
Order By: Relevance
“…Chang, 2010;Ghaddar et al, 2012;Lam and Yang, 2014;Shih et al, 2016;Sørensen et al, 2015) is difficult, since the studies in question may be measuring various constructs of HL. Previous research has shown that the tool used to measure HL has an influence on the level of HL identified (Barber et al, 2009).…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Chang, 2010;Ghaddar et al, 2012;Lam and Yang, 2014;Shih et al, 2016;Sørensen et al, 2015) is difficult, since the studies in question may be measuring various constructs of HL. Previous research has shown that the tool used to measure HL has an influence on the level of HL identified (Barber et al, 2009).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The findings reflect a good general literacy level among young people in those areas (UNESCO, 2014c). Interestingly, when another study in the same area of Asia assessed HL -via an instrument which addressed the broader construct of HL -the proportion of children with low HL was higher, at over 25% (Shih et al, 2016). This is consistent with the view that functional HL tools such as Test of Functional Health Literacy in Adults (TOFHLA; Parket et al, 1995) and Rapid Estimate of Adult Literacy in Medicine (REALM; Davis et al, 1991) focus on phenomena (e.g.…”
Section: The Level Of School-aged Children's Hl -What Have We Learnedmentioning
confidence: 99%
See 1 more Smart Citation
“…Jednotlivé údaje jsou uvedeny v tabulkách 1 a 2. Z 19 analyzovaných studií bylo nejvíce amerických [6-8, 11, 12, 15-18, 20-22, 24], dále pak z Tchaj-wanu [9,10,23], z Číny [13], z Izraele [14] a Finska [19]. Evaluací zdravotní gramotnosti se v rámci 8 evropských států zabývali Pelikan et al [25], přičemž do této skupiny byli zařazeni i respondenti od 15 let.…”
Section: Výsledky a Diskuseunclassified
“…Sběr dat probíhal jednak v prostředí základních a středních škol za spolupráce vyškolených pedagogických pracovníků [9,10,13,14,18,19,23,24], ve zdravotnických zařízeních [6,11,15,16,21], přímo v komunitě [8,16,20]. V ostatních analyzovaných studiích nebyl způsob sběru popsán.…”
Section: Prostředí Výzkumu a Použité Hodnoticí šKály Zdravotní Gramotunclassified